ECOLOGICAL CITIZENSHIP MOVEMENT AS AN EFFORT TO CREATE ENVIRONMENTALLY CARING COMMUNITY BEHAVIOR - Setyarini, Dyah (International Conference On Social Science Education, 2023)
Indonesia is one of the countries currently experiencing environmental damage issues, mainly caused by industrial progress in big cities, such as forest logging without selective logging, waste disposal without management, and a lack of physical development balanced with sustainable environmental conservation efforts. Good citizens know active participation and a civic character that cares about the environment. Therefore, the importance of efforts to form ecological citizenship, which in essence is the ethical and moral procedures of citizens towards their environment responsibly, can be wise in protecting, managing and preserving the environment. This article discusses forms of movement, Ecological citizenship, and the formation of environmentally conscious public behaviour. The method used in this paper is library research. Movement Ecological citizenship is carried out through the post-reclamation movement mining, mangrove planting movement, resistance movement, and waste awareness movement. Efforts to build environmentally caring character are instilled through environmental education in society and students in schools, clear law enforcement for mining companies, and campaigns via social media regarding environmental conditions.